2020
DOI: 10.36834/cmej.67870
|View full text |Cite
|
Sign up to set email alerts
|

Improving the LGBTQ2S+ cultural competency of healthcare trainees: Advancing health professional education.

Abstract: Background: Lesbian, Gay, Bisexual, Trans, Queer, and Two-spirit (LGBTQ2S+) populations experience worse health outcomes compared to age-matched heterosexual and cisgender peers. Health professionals’ deficient knowledge and negative attitudes can contribute to these inequities. Healthcare trainees report insufficient LGBTQS2+ cultural competence training. Methods: In this prospective, mixed-methods pre-post design, Atlantic Canadian health students were tested on knowledge, attitudes and self-reported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Inclusive teaching focuses on creating learning environments that enable students to effectively construct knowledge by leveraging student experience, attitude, motivation, confidence, and participation [ 6 , 21 , 22 ]. The findings of our evaluation align with other studies that indicate a desire for more inclusive training and illustrate positive participant perceptions associated with culturally related training [ 8 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Preceptors in our study, for example, indicated that they desired more inclusive training, which aligns with the results of a previous preceptor needs assessment [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Inclusive teaching focuses on creating learning environments that enable students to effectively construct knowledge by leveraging student experience, attitude, motivation, confidence, and participation [ 6 , 21 , 22 ]. The findings of our evaluation align with other studies that indicate a desire for more inclusive training and illustrate positive participant perceptions associated with culturally related training [ 8 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Preceptors in our study, for example, indicated that they desired more inclusive training, which aligns with the results of a previous preceptor needs assessment [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Seventy-six percent of studies ( 8 , 13 , 14 , 23 , 28 , 35 38 , 48 , 51 , 58 , 59 , 77 , 82 , 94 , 96 , 99 , 109 ) instructed on structural determinants such as structural racism and/or historic oppression of groups so that subjects could explore explicit and implicit biases. All these studies demonstrated an increased awareness of bias, and subjects often voiced a willingness to address their biases.…”
Section: Novel Intervention Contentmentioning
confidence: 99%
“…All these studies demonstrated an increased awareness of bias, and subjects often voiced a willingness to address their biases. Four studies explored the use of contact with groups with identities such as LGBTQI ( 58 , 59 ) and persons with mental illness ( 27 , 77 ) with positive and negative results, respectively.…”
Section: Novel Intervention Contentmentioning
confidence: 99%
“…Although higher levels of knowledge regarding SGM individuals have been found to be correlated with more positive attitudes towards SGM persons [ 9 ], individual cases of discrimination in healthcare can be based on healthcare professionals’ moral convictions and attitudes. Other barriers include high costs, e.g., for the specific interventions transsexual individuals need, lack of availability of specific health services, former negative experiences in healthcare settings, prejudice amongst healthcare professionals, unfavorable communication between healthcare providers and patients, discrimination and stigmatization, and insurance-related issues such as the unwillingness of insurance companies to pay for transgender-related care or gaps in healthcare insurance coverages [ 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. There is a considerable systemic aspect to discrimination and the restriction of access to healthcare.…”
Section: Introductionmentioning
confidence: 99%